Health Care Systems in Spain and Portugal – Economic Approach (Economic and Political Thought, 2019)
The article is a preliminary analysis of the economic conditions of healthsystems in Spain and Portugal. It describes their organisational structures andlists entities functioning in them. It presents changes that have taken placein the economic situation of both countries in recent years (including theimpact of the global financial crisis that began in 2008) and the consequencesthat these changes have had for their health policy. The article lists thebasic numbers referring to both systems and describes some organisationalsolutions improving their effectiveness. It also presents elements derivedfrom before the democratic transformation, lowering this efficiency. Probablythe most important of them are separate ‘subsystems’ of health care forsome professional groups (including, for example, administration, thejudiciary and army employees), which collaborate with common health care,but also hinder its uniform and clear operation. Probably to a large extent,as a result of leaving these elements in both systems and the related lackof sufficient optimisation of their operation, Portugal holds the 13th andSpain the 19th position in the European ranking of health systems – theEuro Health Consumer Index – examining these systems using fifty detailedcriteria. A permanent prescription, used in Spain for many years, is worthyof more thorough research and transfer to the Polish healthcare system as itsignificantly reduces doctors’ workload not directly related to treatment, andconsequently their shortage.
Keywords: health care systems, Portugal, Spain, economic approach, organisation, economics